Proceedings of the Thirteenth Conference on Applied Linguistics (CONAPLIN 2020) 2021
DOI: 10.2991/assehr.k.210427.079
|View full text |Cite
|
Sign up to set email alerts
|

Personal Metadiscourse Features on TED Talks by British Speakers

Abstract: The present research aims to analyze types and functions of personal metadiscourse used by native speakers (British) during their performance on TED Talks. The study applied Ädel's (2006) taxonomy of personal metadiscourse in academic discourses to capture the occurrences of personal metadiscourse. Personal metadiscourses (I, we, you) are commonly applied in written language. Only a few of them can be found in spoken language. Once there is the spoken one, they are typically performed in monologue setting, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It is found that pronoun "You" is rarely used while pronoun I is mostly used by British speakers in discourse organization for exemplifying. Pronoun "You" and "We" are used in audience interaction category for managing messages (Duwila & Probowati, 2021). In analyzing the types of deixis and the referent of deixis in this study, the writer only focus on looking at the types of deixis and placing them according to the group then with the referents to each word.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that pronoun "You" is rarely used while pronoun I is mostly used by British speakers in discourse organization for exemplifying. Pronoun "You" and "We" are used in audience interaction category for managing messages (Duwila & Probowati, 2021). In analyzing the types of deixis and the referent of deixis in this study, the writer only focus on looking at the types of deixis and placing them according to the group then with the referents to each word.…”
Section: Introductionmentioning
confidence: 99%